Evaluation of bone mineral density and body compositions interrelation in young and middle-aged male patients with Crohn’s disease by quantitative computed tomography - Zhang, Xueli; Peng, Kun; Li, Gang; Wan, Lidi; Xu, Tingting; Cui, Zhijun; Xiao, Fuxia; Li, Li; Liu, Zhanju; Zhang, Lin; Tang, Guangyu (Frontiers in Endocrinology, 2022)
Background: The aim of this study was to investigate the characteristics of bone mineral density (BMD) and body compositions, as well as the impact of body compositions on BMD in young and middle-aged male patients with Crohn’s disease (CD). Methods: Patients with CD (n = 198) and normal controls (n = 123) underwent quantitative computed tomography (QCT) examination of lumbar vertebra 1-3 (L1-3). The BMD and bone geometric parameters were measured and outputted by QCT post-process software. Meanwhile, body composition parameters, including subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), lean mass (LM) and muscles mass around lumbar vertebrae were also acquired by QCT. Blood indicators (IL-6, IL-8, TNF-α, CRP, Ca, P) were collected from clinical medical records. Independent t-test was used to compare these variables between CD group and normal control group. Results: There was no significant difference in age, height and weight between CD group and control group (P > 0.05), indicating that the sample size was relatively balanced. Mean BMD in CD group were lower than those in control group, but the difference was not statistically significant (P > 0.05). The bone geometric parameters microarchitecture of the CD group, including cortical area/density (Ct. Ar, Ct. BMD) and trabecular area/density (Tb. Ar, Tb. BMD), were significantly lower than those of the control group (P < 0.05). So were the body composition parameters including TAT, VAT, SAT, LM and muscles mass (P < 0.05). Besides, the level of plasma IL-6, IL-8, CRP and TNF-α of the CD group were higher than those of the control group (P < 0.05). On the contrary, the BMI, serum Ca and P levels of the CD group were lower than those of the control group (P < 0.05). Through multiple linear regression analysis, Tb. BMD, VAT, Ct. Ar, LM, Ca and IL-8 entered the regression model and revealed a significant contribution to BMD. Conclusions: Patients with CD could suffer from reduction of BMD. However, the parameters of bone geometric parameters are more sensitive and accurate than BMD changes. Among them Tb. BMD, VAT, Ct. Ar, LM have significant effects on BMD reduction.